Novel S2 subunit-specific antibody with broad neutralizing activity against SARS-CoV-2 variants of concern - Heo, Chang-Kyu; Lim, Won-Hee; Yang, Jihyun; Son, Sumin; Kim, Sang Jick; Kim, Doo-Jin; Poo, Haryoung; Cho, Eun-Wie (Frontiers in Immunology, 2023)
Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), had a major impact on both the global health and economy. Numerous virus-neutralizing antibodies were developed against the S1 subunit of SARS-CoV-2 spike (S) protein to block viral binding to host cells and were authorized for control of the COVID-19 pandemic. However, frequent mutations in the S1 subunit of SARS-CoV-2 enabled the emergence of immune evasive variants. To address these challenges, broadly neutralizing antibodies targeting the relatively conserved S2 subunit and its epitopes have been investigated as antibody therapeutics and universal vaccines. Methods We initiated this study by immunizing BALB/c mice with β-propiolactone-inactivated SARS-CoV-2 (IAV) to generate B-cell hybridomas. These hybridomas were subsequently screened using HEK293T cells expressing the S2-ECD domain. Hybridomas that produced anti-S2 antibodies were selected, and we conducted a comprehensive evaluation of the potential of these anti-S2 antibodies as antiviral agents and versatile tools for research and diagnostics. Results In this study, we present a novel S2-specific antibody, 4A5, isolated from BALB/c mice immunized with inactivated SARS-CoV-2. 4A5 exhibited specific affinity to SARS-CoV-2 S2 subunits compared with those of other β-CoVs. 4A5 bound to epitope segment F1109–V1133 between the heptad-repeat1 (HR1) and the stem-helix (SH) region. The 4A5 epitope is highly conserved in SARS-CoV-2 variants, with a significant conformational feature in both pre- and postfusion S proteins. Notably, 4A5 exhibited broad neutralizing activity against variants and triggered Fc-enhanced antibody-dependent cellular phagocytosis. Discussion These findings offer a promising avenue for novel antibody therapeutics and insights for next-generation vaccine design. The identification of 4A5, with its unique binding properties and broad neutralizing capacity, offers a potential solution to the challenge posed by SARS-CoV-2 variants and highlights the importance of targeting the conserved S2 subunit in combating the COVID-19.